Effects of Interleukin-12 and Interleukin-15 on Measles-Specific T-Cell Responses in Vaccinated Infants - GANS, HAYLEY A. (Mary Ann Liebert, Inc., 2008)
Understanding the infant host response to measles vaccination is important because of their increased mortality from measles and the need to provide effective protection during the first year of life. Measles-specific T- and B-cell responses are lower in infants after measles vaccination than in adults. To define potential mechanisms, we investigated age-related differences in measles-specific T-cell proliferation, CD40-L expression, and IFN-γ production after measles immunization, and the effects of rhIL-12 and rhIL-15 on these responses. Measles-specific T-cell proliferation and mean IFN-γ release from infant PBMCs were significantly lower when compared with responses of vaccinated children and adults. Infant responses increased to ranges observed in children and adults when both rhIL-12 and rhIL-15 were added to PBMC cultures. Furthermore, a significant rise in T-cell proliferation and IFN-γ release was observed when infant PBMCs were stimulated with measles antigen in the presence of rhIL-12 and rhIL-15 compared to measles antigen alone. CD40-L expression by infant and adult T cells stimulated with measles antigen was comparable, but fewer infant CD40-L(+) T cells expressed IFN-γ. These observations suggest that lower measles-specific T-cell immune responses elicited by measles vaccine in infants may be due to diminished levels of key cytokines.